Management of the prevention of risks at work and the state of self-perceived health - Garay-Cabrera, Gianny R. (2020)
The objective of the research was to relate the management of risk prevention at work with the self-perceived health status of the nursing professionals of a Public Hospital in Huánuco in 2018. It was a quantitative, analytical, prospective, cross-sectional study and of correlational design, with a sample population of 46 nurses, who satisfactorily answered the previously validated and reliable documentary instruments. The descriptive analysis and the hypothesis of contrast were carried out by means of the Chi square; for a confidence level of 95% and p ≤ 0.05. The results indicate that the level of risk prevention management at work was perceived by the majority of the sample at the moderate level [71.7% (33)], which implies that in some way the design of plans was carried out of risk prevention, they have a certain capacity for risk prevention management, they carry out planned medical controls, work protection actions, vaccination coverage, information and training on risk prevention and preventive information from Occupational Risk Insurers. Physical health status was perceived as better [76.1% (35)], while mental health status was perceived to be worse range [89.1% (41)]. It is concluded that the management of risk prevention at work is related to the self-perceived state of physical and mental health by nursing professionals. In other words, given the management of risk prevention at a moderate level, the perception of health status is worse and in opposite directions1.